(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Currently, the factor of chemical pollution of the environment is one of the priority risk factors for public health and a factor that largely determines the level of sanitary and epidemiological well-being of the population. The growing chemical pollution of the environment, especially atmospheric air, combined with a decrease in the intensity of supervision over its parameters institutions, creates a direct threat to the deterioration of public health. Ambient air pollution is one of the most serious environmental factors affecting the health of everyone in low-, middle- and high-income countries. In 2019, ambient (outdoor air) pollution in both urban and rural areas was estimated to cause 4.2 million premature deaths worldwide; this mortality is due to exposure to fine particulate matter, which leads to the development of cardiovascular, respiratory and cancer diseases. WHO estimates that in 2019, about 37% of premature deaths associated with air pollution occurred as a result of coronary heart disease and stroke, 18% and 23% as a result of chronic obstructive pulmonary disease and acute lower respiratory tract infections, respectively, and 11% - as a result of cancer of the respiratory tract. People living in low- and middle-income countries bear a disproportionate burden of disease caused by outdoor air pollution: these areas account for 89% of cases (of the 4.2 million premature deaths). The highest disease burden is found in the WHO South-East Asia and Western Pacific regions. Recent estimates of the burden of disease indicate a major role of air pollution in the development of cardiovascular diseases, including fatalities.